PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP INTELLECTUAL CAPITAL PERFORMANCE - Purwanto, Agus (PRESTASI, 2011)
This research toward to know the affect of ownership structure on intellectual capital performance.t Ownership strucuture that used in this research is family ownership, managerial ownership and institutional ownership. Population that use in this research is 402 banking company listed in Indonesian Stock Exchange. Based on purposive sampling methode,there are 60 sample used in this research. This research used multiple regression that acccompany with classic assumption test which contain of normalitas test, multikolinearitass test,autocorelation test, and heteroskedasitas test. The research used the parsial test to know each independent variabel have significantly effect to intellectual capital performance. Data was analized by SPSS 17 with signifikant level 5%.The result show that family ownership and managerial ownership significantly did not influence to intellectual capital performance. However, institutional ownership significantly influence to intellectual capital performance.Keyword: intellectual capital performance, ownership structure, family ownership, managerial ownership, institutional ownership